A SIMULATION-BASED DEA FRAMEWORK TO IMPROVE CUSTOMER’S WAITING TIME AT VEHICLE INSPECTION CENTRE - Khir Johari, Nur Syamimi; Ahmad, Norazura; Zainal Abidin, Norhaslinda (Journal of Technology Management and Business, 2018)
A long queue and waiting time have become the most common issue that usually happened at service industry. Similarly, in a vehicle inspection centre (VIC), a higher quality of service is measured by a short and acceptable waiting time. Typically, the long waiting time among customers is resulted by some factors, which are customer arrivals, human factors, and maintenance strategy. However, this study only focuses on customer arrival factor that contributed to this problem. This paper is a review of work based on a study conducted at VIC in Selangor, Malaysia. A framework of simulation-based DEA model is proposed to determine the most efficient strategy to reduce the problem of customer waiting time at VIC. The developed framework aims to help the management in decision making to improve the operation of the VIC current system in future.